A SYSTEMATIC REVIEW: ASUPAN ZAT GIZI MAKRO DAN STATUS GIZI PASIEN KANKER YANG MENJALANI KEMOTERAPI A Systematic Review: Macro Nutrient Intake and Nutritional Status of Cancer Patients Undergoing Chemotherapy - Sheryll Deby Regyna; Merryana Adriani; Qonita Rachmah (Universitas Airlangga, 2021)
Nutrient intake in cancer patients is diff erent from other disease due to side eff ects of chemotherapy, like nausea, vomit, and appetite loss, which in the long run it have an impact on the nutritional status of patients. The study used systematic reviews to determine side eff ects of chemotherapy on macro nutrient intake and nutritional status of cancer patients in 15 literature. Those literatures were taken from articles published from 2005 to 2019 in PubMed, NCBI, and Google Scholar and all of them were using observational research design. The results of 15 literature showed, there was a decrement in macro nutrient intake including energy, carbohydrates, protein, and fat as a result of chemotherapy side eff ects such as nausea, vomit, and appetite loss. Ten of 15 literature showed the patient nutritional status was underweight, and 5 literature showed overweight and obesity due to the use of corticosteroids as supporting treatment. The future research opportunities that can be carried out a deeper analysis of the relationship of nutritional intake and changes in nutritional status of patients with longer duration for the research, measurement methods by using gold standards which are weighing food record, as well as diff erent types of cancer.